Strategi Coping Pasca Perceraian: Tinjauan Psikologi Klinis dan Kesehatan Mental Dunia - Zuhdiyah Izzatun Nisa; Tristiadi Ardi Ardani (CV. Lentera Literasi Indonesia, 2026)
Global mental health has become a crucial issue in the modern world, with WHO (2023) reporting that one in four individuals experiences a mental disorder. Divorce is among the most significant psychological stressors affecting emotional and social well-being. This study aims to analyze post-divorce coping strategies from a clinical psychology perspective and their relevance to global mental health. The method employed is a literature review of national and international publications over the past ten years. Findings indicate that adaptive coping strategies, both problem-focused and emotion-focused play a vital role in enhancing resilience and reducing the risk of mental disorders. Cross-theoretical analysis of Freud, Bowlby, Lazarus & Folkman, and Rogers reveals that post-divorce recovery involves intrapsychic dynamics, emotional attachment, cognitive adaptation, and self-acceptance. Thus, effective coping strategies constitute a significant contribution to strengthening global mental health through clinical psychology approaches that emphasize empathy and cultural sensitivity.